2009
DOI: 10.1093/rpd/ncp147
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of uranium in drinking water and associated age-dependent radiation dose in India

Abstract: Exposure due to natural radiation is of particular importance because it accounts for the largest contribution (nearly 85 %) to the total collective dose of the world population. An attempt has been made to present the feasibility of uranium occurrence in drinking water samples from different states of India, by laser-induced fluorimetry. The associated age-dependent radiation dose was estimated by taking the prescribed water intake values of different age groups. The concentration of uranium obtained, i.e. 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Sahoo et al, has been reported U concentration in the range of 0.1-19.6 lg l -1 in the drinking water samples collected from Orissa, Andhra Pradesh, Maharashtra, Madhya Pradesh, Kerala etc. [13], U concentration around uranium mining and processing facility of the Jaduguda, Jharkhand has been reported in the range of 0.5-28 lg l -1 [15] and around Narwapahar U mine in Jharkhand it has been in the range of 0.1-3.75 lg l -1 [14]. Further around the proposed U mining sites located at Lambapur and Pedagattu in the Nalgonda district of Andhra Pradesh, it has been reported in the range of 0.2-77.4 lg l -1 [18].…”
Section: Comparison Of U Concentration With Worldwide Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sahoo et al, has been reported U concentration in the range of 0.1-19.6 lg l -1 in the drinking water samples collected from Orissa, Andhra Pradesh, Maharashtra, Madhya Pradesh, Kerala etc. [13], U concentration around uranium mining and processing facility of the Jaduguda, Jharkhand has been reported in the range of 0.5-28 lg l -1 [15] and around Narwapahar U mine in Jharkhand it has been in the range of 0.1-3.75 lg l -1 [14]. Further around the proposed U mining sites located at Lambapur and Pedagattu in the Nalgonda district of Andhra Pradesh, it has been reported in the range of 0.2-77.4 lg l -1 [18].…”
Section: Comparison Of U Concentration With Worldwide Valuesmentioning
confidence: 99%
“…In India several studies have also been conducted to estimate natural U concentrations in groundwater around different proposed and operational U deposits and also in general areas where a wide range of U concentrations have been reported. [13][14][15][16][17][18]. The major objectives of the present study are to estimate U concentration in groundwater in the surrounding environment of the U mining and processing facility and associated health risk, if any, to local population through ingestion of water.…”
Section: Introductionmentioning
confidence: 99%
“…The detector is placed at a right angle to the radiation source to avoid the background signal. The laser source emits an intense pulsed ultraviolet radiation of 337.1 nm carrying energy of 20 µJ of width 7 ns with a repetition time of 10 pulses per second (Sahoo et al, 2009). Fluorescence interference due to organic matter is removed by using a proper electronic delay, optical filter and gating technology (Veselsky et al, 1988).…”
Section: Sample Preservation and Analysismentioning
confidence: 99%
“…D1 is fluorescence due to the sample only, D2 is fluorescence due to the sample and spiked uranium standard, V1 is the volume of U standard added, V2 is the volume of sample taken and C is the concentration of the U standard solution (Sahoo et al, 2009). …”
Section: Analytical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation